Environmental and Occupational Factors Associated with Leptospirosis: A Systematic Review - Mazni Baharom; Norfazilah Ahmad; Rozita Hod; Mohd Hasni Ja’afar; Fadly Syah Arsad; Fredolin Tangang; Rohaida Ismail; Norlen Mohamed; Mohd Firdaus Mohd Radi; Yelmizaitun Osman (Heliyon, 2024)
Background: Leptospirosis is a neglected emerging zoonotic disease with a profound public health impact worldwide with higher burden of disease in resource-poor countries. The environmental and occupational exposures contribute to human and animal transmission, but the interaction was less explored. A deeper understanding of the critical environmental and occupational drivers in different contexts will provide useful information for disease control and prevention measures. Objective: This review aimed to summarize the potential environmental and occupational risk factors associated with leptospirosis infection. Methods: Four databases (Scopus, Web of Science, Ovid MEDLINE, EBSCOhost) were searched for articles published from 2012 to 2021. Eligible articles were assessed using a checklist for assessing the quality of the studies. The quality of the articles was assessed based on the laboratory diagnosis approach and statistical analysis method. Results: A total of 32 studies were included in this systematic review. Water-related risk factors such as natural water as the primary water source (AOR 1.8–18.28), water-related recreational activities (AOR 2.36–10.45), flood exposure (AOR 1.54–6.04), contact with mud (AOR 1.57–4.58) and stagnant water (AOR 2.79–6.42) were associated with increased risk of leptospirosis. Infrastructural deficiencies such as un-plastered house walls and thatched houses presented a higher risk (AOR 2.71–5.17). Living in low-lying areas (AOR 1.58–3.74), on clay loam soil (OR 2.72), agricultural land (OR 2.09), and near rubber tree plantations (AOR 11.65) is associated with higher risk of leptospirosis. Contact with rats (AOR 1.4–3.5), livestock (AOR 1.3–10.4), and pigs (AOR 1.54–7.9) is associated with an increased risk of leptospirosis. Outdoor workers (AOR 1.95–3.95) and slaughterhouse workers (AOR 5.1–7.5) have higher risk of leptospirosis. Conclusion: The environmental and occupational components related to water, infrastructure, landscape, agriculture, and exposed animals play an essential role in leptospirosis transmission. The magnitude of those risk factors differs with geographical region, climate factor, urbanization and population growth, and the country’s socioeconomic status.